Persistence of Only a Minute Viable Population in Chlorotic Microcystis aeruginosa PCC 7806 Cultures Obtained by Nutrient Limitation. - Diogo de Abreu Meireles; Jan Schripsema; Andrea Cristina Vetö Arnholdt; Denise Dagnino (PLoS ONE, 2015)
Cultures from the cyanobacterial strain Microcystis aeruginosa PCC 7806 submitted to nutrient limitation become chlorotic. When returned to nutrient rich conditions these cultures regain their green colour. The aim of this study was to verify whether the cells in these cultures could be considered resting stages allowing the survival of periods of nutrient starvation as has been reported for Synechococcus PCC 7942. The experiments with Microcystis were carried out in parallel with Synechococcus cultures to rule out the possibility that any results obtained with Microcystis were due to our particular experimental conditions. The results of the experiments with Synechococcus PCC 7942 cultures were comparable to the reported in the literature. For Microcystis PCC 7806 a different response was observed. Analysis of chlorotic Microcystis cultures by flow cytometry showed that the phenotype of the cells in the population was not homogenous: the amount of nucleic acids was about the same in all cells but only around one percent of the population emitted red autofluorescence indicating the presence of chlorophyll. Monitoring of the reversion of chlorosis by flow cytometry showed that the re-greening was most likely the result of the division of the small population of red autofluorescent cells originally present in the chlorotic cultures. This assumption was confirmed by analysing the integrity of the DNA and the membrane permeability of the cells of chlorotic cultures. Most of the DNA of these cultures was degraded and only the autofluorescent population of the chlorotic cultures showed membrane integrity. Thus, contrary to what has been reported for other cyanobacterial genera, most of the cells in chlorotic Microcystis cultures are not resting stages but dead. It is interesting to note that the red autofluorescent cells of green and chlorotic cultures obtained in double strength ASM-1 medium differ with respect to metabolism: levels of emission of red autofluorescence are higher in the cells of green cultures and the ability to convert fluorescein diacetate of these cells are heterogeneous when compared to the autofluorescent cells of chlorotic cultures. Thus, the small population of the red autofluorescent cells of chlorotic cultures are in a differentiated metabolic state that allow them to persist in conditions in which most of the population loses viability; persistent cells can be detected in chlorotic cultures maintained for more than a year.